The disciplining of scientific communities. (1st June 2013) - Bulpin, Kate; Molyneux-Hodgson, Susan
Abstract : Amidst ongoing concern with training students in the skills and knowledge necessary to contribute towards a knowledge-intensive economy, we explore how particular 'epistemic subjects' are produced within specific epistemic communities. We examine how social studies of science have probed the 'disciplining' practices that constitute scientific knowledge production, but have tended to overlook how students participate in, and become members of, epistemic communities. We propose that training contexts provide a window onto the disciplining processes through which scientific fields and their practitioners are co-produced. We offer an empirical example of an emerging scientific field that is working to establish community boundaries through the recruitment and training of university students. We explore how newcomers' practices, values and identities are disciplined through participation in this nascent community whilst remaining open to negotiation and resistance. The conclusion calls for more scholarly attention to educational trajectories as processes through which disciplines and their disciples are produced.